A numerical solution of the Klein-Gordon equation and convergence of the decomposition method - Kaya, D; El-Sayed, SM (Elsevier Science Inc, 2004)
The decomposition method for solving the Klein-Gordon equation has been implemented. The explicit and numerical solutions of the equation are calculated in the form of convergent power series with easily computable components. The present method performs extremely well in terms of accuracy, efficiency, simplicity, stability and reliability. We also proved the convergence of Adomian's decomposition method for the nonlinear Klein-Gordon equation. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: decomposition method; modified decomposition method; convergence of the decomposition method; nonlinear Klein-Gordon equations